The Link between Internal Control Mechanisms and Corporate Performance: A study for a New Perspective to Support Economic Growth - Alabdullah, Tariq Tawfeeq Yousif (The International Journal of Accounting and Business Society, 2023)
Purpose — By examining the link between board diversity—defined by gender, the number of members in the board, and the number of independent managers—and its effect on company growth in developing nations, especially in the context of Oman, this study aims to reveal a previously unnoticed conjunction within the accounting, management, and economic fields. Design/methodology/approach — To accomplish this goal, data from 30 industrial and service companies in the non-financial sector listed on the Muscat Securities Market (MSM) for the year 2021 were evaluated using a multiple regression method. Findings — The study's findings showed that the market share of non-financial enterprises in the Muscat market was negatively correlated with board size. On the other hand, market share was significantly and favorably impacted by independent boards, diverse boards, and large boards. Interestingly, the market share of non-financial enterprises was not significantly impacted by firm size, which was considered a control factor. Practical implications – Scholars, legislators, and executives in the business sector involved in emerging markets should all take note of these findings since they have significant practical ramifications. In Oman and may be in similar situations, the research emphasizes the importance of board diversity in promoting business success, as indicated by market share for non-financial enterprises.  Originality/value—As the first study to examine the connection between board diversity and the expansion (measured by market share) of non-financial enterprises in the Middle East, with a particular emphasis on Oman, this research adds to the body of knowledge already in existence. The study provides insightful information about the global conversation about how a diverse board affects an organization's profitability and market share.